Bottom-up control of fertilization on soil nematode communities differs between crop management regimes. (April 2016) - Liu, Ting; Whalen, Joann K.; Ran, Wei; Shen, Qirong; Li, Huixin
Abstract: We evaluated how fertilization impacted nematode trophic groups via changes in trophic resources (soil microbes, plant roots) and the soil environment in a 3-year fertilization experiment in a double-cropped paddy rice and upland wheat agroecosystem. Fertilization exerted a strong influence on bacterial- and fungal-feeding nematodes by changing soil microbes and the soil environment in both phases, whereas plant- and root-associated fungal-feeding nematodes were bottom-up controlled by plant roots in the upland wheat phase only. Also, fertilization-induced linkages between bacteria phyla and bacterial-feeding nematode genera were inconsistent across crop phases. Although fertilization results in bottom-up control of nematode feeding groups in well-drained soils, our findings suggest environmental filtering due to water management and crop species can be responsible for the abundance of dominant nematode genera. Highlights: Fertilization exert bottom-up control of soil nematodes in well-drained soils. Plant- and fungal-feeders were controlled by plant roots in upland field only. Microbial feeders were more affected by soil environment in upland than paddy field. Environmental filtering is responsible for the number of dominant nematode genera.